2020
DOI: 10.1534/g3.120.401511
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of DNA Methylation Dynamics on the Mutation Rate During Human Germline Development

Abstract: DNA methylation is a dynamic epigenetic modification found in most eukaryotic genomes. It is known to lead to a high CpG to TpG mutation rate. However, the relationship between the methylation dynamics in germline development and the germline mutation rate remains unexplored. In this study, we used whole genome bisulfite sequencing (WGBS) data of cells at 13 stages of human germline development and rare variants from the 1000 Genome Project as proxies for germline mutations to investigate the correlation betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 48 publications
7
25
0
Order By: Relevance
“…The cytosine in the CpG site is often methylated to form 5-methylcytosine, which undergoes deamination as a result of spontaneous oxidation 18 , 23 . It has been suggested that higher methylation levels are associated with higher mutation rates of CpG dinucleotides during germline development 37 . Therefore, a FD diet could lead to a globally lower methylation level and fewer genome-wide G:C>A:T transitions.…”
Section: Discussionmentioning
confidence: 99%
“…The cytosine in the CpG site is often methylated to form 5-methylcytosine, which undergoes deamination as a result of spontaneous oxidation 18 , 23 . It has been suggested that higher methylation levels are associated with higher mutation rates of CpG dinucleotides during germline development 37 . Therefore, a FD diet could lead to a globally lower methylation level and fewer genome-wide G:C>A:T transitions.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of the effects of DNA methylation on mutation varies widely. The risk of spontaneous oxidative deamination of 5mC to T (or C to U) is relatively well understood, and has been documented to occur in organisms ranging from bacteria ( 46 ) to humans ( 47 ). However, our focus here has been on the effects of 5mC methylation on the binding of specific proteins, and on how that protein binding modulates the mutation rate.…”
Section: Discussionmentioning
confidence: 99%
“…One such genomic feature is the spontaneous deamination of 5-methyl cytosine at CpG sites, which has been suggested to cause C to T transitions. The recent development of CpG maps in human germ cells, including primordial germ cells [60] , [61] , have facilitated both cell-type and site-specific analyses of mutations rates and provide support for evidence that the methylation status at CpGs correlate with C to T mutations [62] .…”
Section: Genome Stability In Primordial Germ Cells and Other Proliferative Germ Cellsmentioning
confidence: 91%